2019
DOI: 10.1016/j.bej.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated processing of sugarcane bagasse: Arabinoxylan extraction integrated with ethanol production

Abstract: A proof-of-concept project compared extraction of arabinoxylans (AX) from sugarcane bagasse and 19 wheat bran via alkaline hydrogen peroxide followed by enzyme-assisted extraction with 20 combinations of feruloyl esterases and a xylanase. Bagasse contains comparable amounts of AX to 21 wheat bran, but with a much lower arabinoxylan substitution on the xylan backbone (A:X ratio of 22 around 0.2 compared with 0.6 for wheat bran), hence offering AX products with distinctive 23 functionality and potential end uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
21
1
1
Order By: Relevance
“…Both classic and precision breeding of sugarcane varieties have reported xylose contents in the bagasse between 8.8% and 20.4% (Benjamin et al , ). There is considerable interest in hemicellulose applications as they can be used in a range of food and non‐food applications including film forming and as emulsifiers and stabilisers in the food, pharmaceutical and cosmetic industries (Hansen & Plackett, ; Campbell et al , ). Arabinoxylans (AX) are the most abundant hemicelluloses in annual plants and have been identified in a variety of tissues of the major commercial cereals, for example in wheat, barley or rye (Peng et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both classic and precision breeding of sugarcane varieties have reported xylose contents in the bagasse between 8.8% and 20.4% (Benjamin et al , ). There is considerable interest in hemicellulose applications as they can be used in a range of food and non‐food applications including film forming and as emulsifiers and stabilisers in the food, pharmaceutical and cosmetic industries (Hansen & Plackett, ; Campbell et al , ). Arabinoxylans (AX) are the most abundant hemicelluloses in annual plants and have been identified in a variety of tissues of the major commercial cereals, for example in wheat, barley or rye (Peng et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to wheat bran, which also contains 20–30% AX (Maes & Delcour, ; Maes & Delcour, ), the ratio of arabinose to xylose (A:X) is much lower in sugarcane bagasse typically at around 0.2 (de Souza et al , ), while in wheat bran A:X ranges between 0.5 and 0.6 (Courtin & Delcour, ; Ordaz‐Ortiz & Saulnier, ). Reduction in arabinose substitution leads to a more uniform xylan backbone, which is likely to reveal different functional properties compared with AXs from wheat bran, including gel formation capacity, viscosity enhancement or susceptibility to enzymic action, thus impacting their performance in food formulations (Campbell et al , ). However, in contrast to wheat AX, bagasse AX has not ben extensively characterised in order to judge its potential in food applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, after 8 h enzymatic hydrolysis, a significant increase of xylooligomers from DP2 to DP6 was observed independently of the type and dose of xylanase used, except when P xylanase was used, when no generation of DP5 units was detected. Campbell et al (2019) also reported a positive effect of the use of xylanases to reduce the size of AX molecules. Regarding S xylanase, the use of a higher dosage of enzyme increased the amount of xylooligosaccharides with a polymerization degree from DP2 to DP6.…”
Section: Enzymatic Hydrolysis and Characterization Of The Ax Suspensionmentioning
confidence: 94%
“…In order to recover the AX contained in the prehydrolysate of BSG obtained under optimal pretreatment conditions (172 °C and 0.38 M NaOH), a precipitation method based on the addition of ethanol was carried out, using different ratios of prehydrolysate:ethanol (1:1, 1:2 and 1:3 v/v). Ethanol precipitation has been considered a suitable method for AX precipitation, as ethanol can be produced in ABE fermentation and thus enable the economically viable production of AX in an integrated biorefinery (Campbell et al, 2019). Moreover, ethanol can be recovered by distillation, unlike other methods for AX purification, such as the ion-exchange resins, which can only be regenerated using chemical products.…”
Section: Arabinoxylans Recoverymentioning
confidence: 99%
See 1 more Smart Citation